It’s All about the Zone: Spider Assemblages in Different Ecological Zones of Levantine Caves - Jordan P. Cuff (MDPI AG, 2021)
Caves possess a continuum of ecological zones that differ in their microhabitat conditions, resulting in a gradient of nutrients, climate, and illumination. These conditions engender relatively rapid speciation and diverse assemblages of highly specialised spider fauna. It is unclear, however, how zonation of these caves affects spider assemblage composition and structure. Surveys of 35 Levantine caves were conducted to compare the assemblages of spiders between their different ecological zones. The diverse spider assemblages of these caves differed between the entrance, twilight, and dark zones, with troglophiles and accidental species occupying the cave entrance, endemic troglobites occupying the dark zones, and hybrid assemblages existing in the twilight zones. The progression of assemblage composition and divergence throughout cave zones is suggestive of processes of ecological specialisation, speciation, and adaptation of cave-endemic troglobites in the deepest zones of caves, while cave entrance assemblages are composed of relatively common species that can also be found in epigean habitats. Moreover, the cave entrance zone assemblages in our study were similar in the different caves, while the cave dark zone assemblages were relatively distinct between caves. Cave entrance assemblages are a subset of the regional species pool filtered by the cave conditions, while dark zone assemblages are likely a result of adaptations leading to local speciation events.